Workshop Model Pembelajaran Project-Based Learning Berbasis Penggunaan ICT bagi Guru SMAN 2 Kampar Kiri Tengah - Marwa Marwa; Herlinawati Herlinawati; Siti Fadillah (Jurnal Pengabdian Pada Masyarakat, 2021)
WORKSHOP ON ICT-BASED PROJECT-BASED LEARNING MODEL FOR TEACHERS OF SMAN 2 KAMPAR KIRI TENGAH. This community service activity was carried out at SMAN 2 Kampar Kiri Tengah in Riau Province due to the lack of knowledge, understanding and creativity of teachers in implementing innovative and creative learning in the classroom so that learning becomes monotonous where students are very dependent on teachers. Therefore, the team seeks to facilitate teachers in improving the quality of learning by implementing project-based learning with ICT use. The methods of implementing this activity begins with a situation analysis stage in the form of field observations and interviews with school principal and teachers, identifying teachers’ problems, providing a training on project-based learning model based on the use of ICT which is continued with questions and answers, discussion followed by providing revisions and suggestions for PBL work papers designed by the teachers with assistance. The results showed that participants could design (1) PBL worksheets, (2) project names and objectives, (3) products produced, (4) time allocation for project completion, (5) ICT facilities used (YouTube links, Google websites, blogs, social media, etc.), and (6) the assignment of students in PBL groups. The PBL projects designed by teachers include instructional videos (Mathematics, Physics, PPKn, Economics), Sociology Glossary, Dictionary/Glossary, Daily Vocabulary Dictionary, Worship Practice Book, Genetic Disease Book, Hero Biography History Book, Geography Glossary, and the chemical product of PBL results. Finally, the community service team concluded that the instructional training with the PBL model based on the use of ICT for teachers of SMAN 2 Kampar Kiri Tengah can provide knowledge, understanding and abilities to participants to design this learning model in their respective subjects.